A puzzle of life: crafting ribosomal subunits - Kressler, Dieter; Hurt, Ed; Baßler, Jochen (Trends in biochemical sciences, 2017)
The biogenesis of eukaryotic ribosomes is a complicated process during which the transcription, modification, folding, and processing of the rRNA is coupled with the ordered assembly of ∼80 ribosomal proteins (r-proteins). Ribosome synthesis is catalyzed and coordinated by more than 200 biogenesis factors as the preribosomal subunits acquire maturity on their path from the nucleolus to the cytoplasm. Several biogenesis factors also interconnect the progression of ribosome assembly with quality control of important domains, ensuring that only functional subunits engage in translation. With the recent visualization of several assembly intermediates by cryoelectron microscopy (cryo-EM), a structural view of ribosome assembly begins to emerge. In this review we integrate these first structural insights into an updated overview of the consecutive ribosome assembly steps.
Gesehen am 25.04.2018